Humanity in the Era of Revolution 4.0:: An Analysis of Artificial Intelligence in the light of Seyyed Hossein Nasr’s Philosophy of Humanity - Owoyemi, Musa Yusuf (STAI Darul Kamal NW Kembang Kerang, 2025)
This paper analyses the issue of artificial intelligence in the light of Seyyed Hossein Nasr philosophy of humanity. It looks at the changing definition and understanding of human being in view of the fourth industrial revolution through the traditional society to the renaissance/modern period and the 21st century. It bases this analysis on the dichotomy between the promethean and pontifical man as espoused in the thought of Seyyed Hossein Nasr and went on to define man anew based on the workings of AI robots in revolution 4.0. Using the qualitative method of critical analysis, it presented the understanding of man as pontifical and promethean as defined by Seyyed Hossein Nasr.